INSECT POLLINATORS/VISITORS OF THREE SELECTED TREES SPECIES AT NGEL NYAKI MOTANE FOREST ,MAMBILA PLATEAU, TARABA STATE NIGERIA - Yoriyo, K. P.; Kela, S.L.; Aliyu, Babale; Adangs, L.K.; Charles, Nsor (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2016)
The study on insects‟ pollinators of three selected trees: Eugenia, Deinbollia and Anthonotha were conducted between the months of November2007 to January 2008 to document visitors and the role and contribution of insects to a stable ecosystem. Of all the visitors recorded Bees were the highest (61%) followed by Butterflies (14.5%). Eugenia sp was found to be visited/pollinated mainly by Bees (Apis mellifera L) (94.6%) in contrast to Deinbollia sp with (42.5%). Anthonotha sp which had seven insect pollinators had butterflies recording the highest visitors (43% ). The high visitation of bees pollinators to Eugenia plant may pose treat to the existence of the tree in the forest, since the forest Ngel Nyaki was faced with danger of crude harvesting of honey. This will consequently lead to a decline in bird‟s population of the area as the tree is a major food source to birds in the forest.